Acute Abdomen in the 17th Week of Twin Pregnancy due to Ovarian Torsion – A Late Complication of IVF - Habek, D.; Bauman, R.; Rukavina Kralj, L.; Hafner, T.; Turudic, T.; Vujisic, S. (Geburtshilfe und Frauenheilkunde, 2016)
Background: A 32-year-old woman with tubal factor infertility due to bilateral laparoscopic salpingectomy conceived twins with in vitro fertilization (IVF). She developed moderate ovarian hyperstimulation syndrome which was treated with anticoagulant therapy. The subsequent course of the twin pregnancy was normal until the 17th week of gestation when she presented to hospital because of a sharp pain in the right lower abdomen which ceased after admission. Case: Except for a single incident of vomiting, patient had no other subjective symptoms. The clinical examination showed tenderness of the lower right abdominal segment on palpation. The surgeon and the urologist found no signs of an acute surgical or urologic condition, and laboratory findings were within normal reference ranges for pregnant women. Two days after admission the pain reappeared; it was now much stronger and colic-like. The pain was initially located supraumbilically but subsequently spread diffusely across the lower abdomen. Abdominal guarding was present and laboratory findings showed an increase in inflammatory parameters. An enlarged and edematous right ovary was found on transvaginal ultrasound. Conclusion: Exploratory laparotomy via a vertical midline abdominal transection revealed a torqued necrotic right ovary with elements of inflammation and inflammatory adhesions involving the entire pelvis. The patient underwent right-sided ovariectomy and adhesiolysis. Recovered was normal and the patient was delivered of healthy twins in the 37th week of gestation.
Keywords: IVF; ovary; torsion; pregnancy